To Leave or Not to Leave? Climate Change, Exit, and Voice on a Pacific Island - Ilan Noy (Center for Economic Studies and ifo Institute (CESifo), 2016)
Observers repeatedly predict that climate change will lead and is already causing massive migration with very large numbers of people forced to leave their homes in cataclysmic waves of climate refugees. Yet, most of the empirical research on the contemporary link between climate change and migration fails to find much evidence of this migration. As climate change has been progressively intensifying for decades, should we not expect these migrations to already be happening? Here, we focus on Tuvalu, a small atoll nation in the South Pacific, that in many respects can serve as the Canary-in-the-Mine for climate change research. If migration driven by climate change is not happening today, Tuvalu may explain why. One plausible reason for this lack of migration is the desire by Tuvaluans to Voice. `Voicing', a concept borrowed from Hirschman's Exit, Voice, and Loyalty, is the advocacy expressing one's wish for change. We present evidence that the atoll nations have decided that their best policy at this point in time is to stay and Voice. If it is not unique to the Pacific atolls, this present choice to prefer Voice to Exit may explain why the evidence on climate-induced migration is so fragile. Tuvalu may be using Voice to attempt to avert dire outcomes, or to strengthen its bargaining position for the inevitable discussions about compensation. Still, the biggest risk may be that the equilibrium mix between Voice and Exit is unstable and that the transition from one strategy to the other may be abrupt—probably in response to a catastrophic natural disaster. In the long-term, sudden and unplanned displacement are always less successful, so advance planning is necessary now, including the financing of alternatives from funding through the Warsaw International Mechanism for Loss and Damage.
Keywords: Q00; 330; migration; climate change